Features of Economic Socialization of Children with Disabilities - Serbova, Olha; Lopatina, Hanna; Alieksieieva, Hanna; Tsybuliak, Natalia (Journal of History Culture and Art Research, 2019)
The article deals with the problems of economic socialization of children with disabilities, adaptation of such children, realization of their life chances, opportunities for self-realization in spite of low efficiency of corrective socio-educational technologies’ implementation. The study revealed the peculiarities and differences in the rates of economic socialization of children with disabilities and physically healthy children, which are conditioned by the circumstances of life and the features of individual psychological and group characteristics of these groups of children. The ways, organizational forms and conditions that allow the inclusion of a disabled child in economic relations are identified; complex diagnostic tools were developed and tested to study the external and internal factors of economic socialization of children with disabilities. In the process of specially organized activity, which includes elements of economic knowledge, self-knowledge, value analysis and real practical actions, it is possible to promote enrichment of values and formation of elements of intrinsic motivation for the economic activity of the child. The effectiveness of the implementation of the developed program of direct and indirect influence on the development of economic ideas and economic behavior using the example of the Department of Early Social Rehabilitation of Children with Disabilities of the Center of Social Assistance and Rehabilitation of the Disabled "Turbota" in Berdiansk, Rivne Educational and Rehabilitation Center "Special Child" of Rivne City Council has been experimentally proved; it was included in the curricula of Berdiansk State Pedagogical University.